Implementation of the Learning Method of Reading and Writing the Qur'an at SD IT Bakti Bakti 2 Nairatul Jannah Padang - Pohan, Abdul Hakim; Aziz, Ahmad; Nelwati, Sasmi; Sabri, Ahmad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This research aims to determine the literacy approach used at SD IT Bakti 2 Nairatul Jannah in reading and writing the Koran. This qualitative investigation was carried out at SD IT Bakti 2 Nairatul Jannah. Through testimonies, interviews, and observations, data is collected. Stars, co-stars, mentors, and scholars are the subjects. The findings of the investigation show that the Tartil and Qiro'aty tutoring systems were used to teach reading and writing the Koran. This method is applied in three steps to teach writing and reading newspapers. The first step is the medication stage, during which the teacher creates teaching materials including reference books and assessment books. The perpetration stage follows, during which the teacher uses the Qiro'aty and Tartil teaching philosophies in classical and semi-classical classrooms. First, the assessment phase, in which the instructor administers an exam to gauge the students' proficiency in reading and writing the Qur'an. Keywords: Reading Method, Writing Method, Al-Qur'an